Board gender diversity and firm financial performance in France: Empirical evidence using quantile difference-in-differences and dose-response models - Ramzi Ben Slama; Aymen Ajina; Faten Lakhal (Cogent Economics & Finance, 2019)
The purpose of this paper is to investigate the relationship between board gender diversity and firm performance under the enabling and voluntary institutional settings in France. We use a Quantile difference-in-differences and dose-response function estimations. The findings show that the comply-or-explain recommendation by the French code is likely to decrease performance for poorly performing firms. However, firm performance increases after the enabling date in high-performing firms. The results of the dose-response functions show that accounting performance reaches a threshold of 40% of women on boards, which coincides with the French law requirements in 2017.
Keywords: 330; Aboard gender diversity; firm performance; enabling approach; quantile difference-in-differences; dose response function